Alternative methods of estimation of reference evapotranspiration in the Yauri station (Cusco, Peru) - Lujano, Apolinario (2019)
Reference evapotranspiration (ΕΤo) is a major component of the hydrological cycle and its estimation is essential for the net irrigation requirement, planning and management of regional water resources. The objective was to evaluate the performance of different empirical methods to estimate the reference evapotranspiration and propose an alternative to estimate the ETo in cases of limitation of meteorological data at the Yauri weather station. The methodology consisted of comparing the results of different empirical methods with the evapotranspiration estimated using the standard method of FAO-56 Penman-Monteith. The performance of the methods was compared using a qualitative evaluation (scatter plots) and quantitative statistical indicators percentage error (PE), root of the mean square error (RMSE), concordance index (d), correlation coefficient (r) and confidence index (c). The results are encouraging for the HS_Berti method because statistically it has an optimal performance with respect to the other methods, with an RMSE=0.22mm / day, PE=3.24%, d=0.29, r=0.95 and c=0.27. It is concluded that the HS_Berti method, having the best performance, can be used as an alternative for the estimation of ETo in cases of limited meteorological data.